Sloth biology: an update on their physiological ecology, behavior and role as vectors of arthropods and arboviruses - Gilmore,D.P. (2001)
This is a review of the research undertaken since 1971 on the behavior and physiological ecology of sloths. The animals exhibit numerous fascinating features. Sloth hair is extremely specialized for a wet tropical environment and contains symbiotic algae. Activity shows circadian and seasonal variation. Nutrients derived from the food, particularly in Bradypus, only barely match the requirements for energy expenditure. Sloths are hosts to a fascinating array of commensal and parasitic arthropods and are carriers of various arthropod-borne viruses. Sloths are known reservoirs of the flagellate protozoan which causes leishmaniasis in humans, and may also carry trypanosomes and the protozoan Pneumocystis carinii.